Design and fabrication of mesoporous heterogeneous basic catalysts - Sun, Lin-Bing; Liu, Xiao-Qin; Zhou, Hong-Cai (Chemical Society reviews, 2015)
Mesoporous solid bases are extremely desirable in green catalytic processes, due to their advantages of accelerated mass transport, negligible corrosion, and easy separation. Great progress has been made in mesoporous solid bases in the last decade. In addition to their wide applications in the catalytic synthesis of organics and fine chemicals, mesoporous solid bases have also been used in the field of energy and environmental catalysis. Development of mesoporous solid bases is therefore of significant importance from both academic and practical points of view. In this review, we provide an overview of the recent advances in mesoporous solid bases, which is basically grouped by the support type and each category is illustrated with typical examples. Cooperative catalysts derived from the incorporation of additional functionalities ( i.e. acid and metal) into mesoporous solid bases are also included. The fundamental principles of how to design and fabricate basic materials with mesostructure are highlighted. The mechanism of the formation of basic sites in different mesoporous systems is discussed as well. Recent advances in mesoporous solid bases were reviewed, and fundamental principles of how to fabricate efficient basic catalysts were highlighted.